1996
DOI: 10.2166/wst.1996.0214
|View full text |Cite
|
Sign up to set email alerts
|

Design options for self-cleansing storm sewers

Abstract: A list of available codes of practice for self-cleansing sewers is presented and a review of appraisals of minimum velocity criterion is summarised. Comparisons of newly developed “minimum velocity” criteria and “minimum shear stress” criterion are presented. Some design charts are also given. These charts are applicable to non-cohesive sediments (typically storm sewers). It appears that sediment size and concentration need to be taken into account, and that a limited depth of sediment bed is recommended for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…(, ), May (), Alvarez (), El‐Zaemey (), Perrusquía (1992a), Perrusquía (1992b), Perrusquía (), Ab Ghani (), Nalluri, Ab Ghani, and El‐Zaemey (), Nalluri et al. (), Nalluri and Ab Ghani (), Ackers et al. (), Butler, May, and Ackers (), Butler et al.…”
Section: Self‐cleansing Design Based On Small Deposit Criterionunclassified
“…(, ), May (), Alvarez (), El‐Zaemey (), Perrusquía (1992a), Perrusquía (1992b), Perrusquía (), Ab Ghani (), Nalluri, Ab Ghani, and El‐Zaemey (), Nalluri et al. (), Nalluri and Ab Ghani (), Ackers et al. (), Butler, May, and Ackers (), Butler et al.…”
Section: Self‐cleansing Design Based On Small Deposit Criterionunclassified
“…It should be emphasized that this occurs only in part full pipe, because in designing the part full flow, the increase in the integrity of bed roughness and the reduction in the discharge capacity can become a problem, although an added hydraulic gradient can be applied. Nalluri and Ghani (1996) showed that the presence of a sediment deposit at limited depth on the bed of the sewer reduces the slope needed to design for all diameters of the used pipes. The limited depth of the deposit considers the amount of the sediment and the specifications of the flow, and shows the actual conditions of the flow in the wastewater conduit.…”
Section: Design Criteria For Limited Deposit Sediment Transportmentioning
confidence: 99%
“…The use of this limited depth criterion requires an accurate performance and strict maintenance of the system, as the condition is quite close to critical. Nalluri and Ghani (1996) suggested further that if wastewater systems of 1 m deep or greater were to be designed as a deposited bed, they could be designed in an efficient manner, so for the sediment transport in pipes of over 1 m or more in diameter they used the equations (Ghani, 1993) …”
Section: Design Criteria For Limited Deposit Sediment Transportmentioning
confidence: 99%
“…Numerous experimental and analytical studies have been done to identify which parameters influence sediment transport (Mayerle et al 1991;Nalluri and Ab Ghani 1996;May 2003;Banasiak 2008;Vongvisessomjai et al 2010;Almedeij 2012;Bonakdari and Ebtehaj 2014a). These studies yielded various equations for determining the limiting velocity.…”
Section: Introductionmentioning
confidence: 99%